2020
DOI: 10.1155/2020/8831138
|View full text |Cite
|
Sign up to set email alerts
|

Area under the Curve-Based Dosing of Vancomycin in Critically Ill Patients Using 6-Hour Urine Creatinine Clearance Measurement

Abstract: Background. The area under the curve- (AUC-) guided vancomycin dosing is the best strategy for individualized therapy in critical illnesses. Since AUC can be calculated directly using drug clearance (CLvan), any parameter estimating CLvan will be able to achieve the goal of 24-hour AUC (AUC24 h). The present study was aimed to determine CLvan based on 6-hour urine creatinine clearance measurement in critically ill patients with normal renal function. Method. 23 adult critically ill patients with an estimated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…26,27 Therefore, it seems that rationalization of vancomycin use requires some appropriate interventions like guideline review sessions besides the application of TDM services. 28,29 In the present study, we found that the duration of hospitalization was significantly shorter in the patients who were correctly treated compared with those who were not. It seems that adherence to guideline recommendations not only prevents the irrational use of antibiotics, but it also improves patients' outcomes.…”
Section: Discussionsupporting
confidence: 48%
“…26,27 Therefore, it seems that rationalization of vancomycin use requires some appropriate interventions like guideline review sessions besides the application of TDM services. 28,29 In the present study, we found that the duration of hospitalization was significantly shorter in the patients who were correctly treated compared with those who were not. It seems that adherence to guideline recommendations not only prevents the irrational use of antibiotics, but it also improves patients' outcomes.…”
Section: Discussionsupporting
confidence: 48%
“…Figure 1E shows deviation points across all NOACs. The risk of a wrong dosage (Figure 1F, mean and 95% CI) was 6.9% (4.8-9.5), 26% (23)(24)(25)(26)(27)(28)(29)(30)(31), 38% (33)(34)(35)(36)(37)(38)(39)(40)(41)(42), and 20% (16)(17)(18)(19)(20)(21)(22)(23) for apixaban, edoxaban, dabigatran, and rivaroxaban, respectively. When pooling the risks, a common risk for incorrect NOAC dosage of 23% (22)(23)(24)(25) when relying on eGFR CKD-EPI was determined from the data.…”
Section: Resultsmentioning
confidence: 99%
“…This has been done for other studies as well. For instance, when dosing vancomycin in critically ill patients, CrCl has been shown to outperform eGFR ( 17 ). While, compared to eGFR approaches, CrCl has the advantage of adding urine creatinine as a second parameter, its accuracy can be impairedby both methodological errors like tubular secretion of creatinine ( 18 ) and execution errors (e.g., collection time and logistics).…”
Section: Discussionmentioning
confidence: 99%
“…The PK of the antibiotics and their plasma concentrations may also be affected as a result of medical interventions such as renal replacement therapy (RRT), extracorporeal membrane oxygenation (ECMO) and plasma exchange (PEX) 9 . Table 1 provides an overview of the PK alterations of antibiotics in patients with sepsis, along with practical dosing recommendations accounting for these alterations 10‐13 …”
Section: Commentmentioning
confidence: 99%
“…Inappropriate dosing of antibiotics is related to the occurrence of serious complications, including adverse drug reactions and the increased number of multidrug‐resistant (MDR) pathogens, as well as poor control of infection 27,28 . Table 2 summarizes the standard/conventional vs. recommended initial doses of the commonly used IV empirical antibiotics in sepsis based on several studies and our routine practice in ICUs 13,29‐31 …”
Section: Commentmentioning
confidence: 99%